Analisis Kualitas Pelayanan Publik Bidang Administrasi (studi kasus pada kantor kecamatan samarinda ilir) - Thomas Bambang Triono (ADMINISTRASI PUBLIK, 2018)
This research is based on the quality of service available in sub-district office of samarinda ilir, with attention to 5 dimension aspects, namely dimension tangibles, Realiability, Responsiveness, Anssurance and Emphaty.The purpose of this study is to determine the quality of public services in the District Office Samarinda Ilir Samarinda City, as well as to determine the supporting factors and inhibiting services in the District Office Samarinda Ilir Samarinda City. The type of research or explanation used is qualitative descriptive used to analyze the relationship between research variables. Types of data used are kusioner, observation, interview, and documentation.From the results of the research, it is found that (1) the quality of public service in Samarinda District Office of Ilir Kota Samarinda has applied dimension of Tangible, Realiability, Responsiveness, Assurance and Emphaty along with its indicator. However, there are some indicators that have not been run in accordance with the wishes of the community, including the inconvenience of service places including incomplete facilities and infrastructure, unskilled employees in using service aids, and unemployment of employees in the service process. (2) Inhibiting factor of public service implementation in Samarinda District Office of Ilir Kota Samarinda is lack of personnel resources and infrastructure facilities. While the supporting factor is the spirit given by employees to each other, held a coordination meeting every three months then give the cultivation of awareness to serve the community with sincerity and in accordance with the conscience. Another supporting factor is the existence of facilities in the form of tools to facilitate the process of service.